Managing discipline and culture-specific knowledge for digitalised, open-access academic discourse: interactive metadiscourse in economics and law research articles. (2nd September 2021) - Tessuto, Girolamo
ABSTRACT: This paper examines the role of interactive metadiscourse in a representative corpus of digitalised, open access social science empirical research articles from the Economics and Law disciplines. Both distributional and functional analyses of interactive metadiscourse resources support a continuum of qualitative and quantitative empirical research analysis methods as necessary to regulate mechanisms for discipline- and culture-oriented knowledge practices in the genre. This study aims to provide a greater understanding of metadiscourse in this incrementally digitalised form of scholarly writing.